Flexible outsourcing, profit sharing and equilibrium unemployment - Erkki Koskela; Jan König (Center for Economic Studies and ifo Institute (CESifo), 2008)
We analyze the questions associated with flexible outsourcing both with committed and flexible profit sharing under imperfect domestic labour markets. How does profit sharing influence flexible outsourcing? What is the relationship between outsourcing cost, profit sharing and equilibrium unemployment, when profit sharing is also a part of the compensation schemes in other industries? In the case of committed profit sharing, outsourcing cost increases wage. Optimal flexible profit sharing is smaller than in the absence of outsourcing, but outsourcing cost and wage will have ambiguous effect on optimal flexible profit sharing. Implementing profit sharing can help to avoid outsourcing due to a direct productivity effect and a wage effect. For equilibrium unemployment the effects of outsourcing cost and profit sharing are ambiguous both in case of committed and flexible profit sharing. In the case of zero effort elasticity there is no committed or flexible profit sharing in the absence or presence of outsourcing and in this case lower outsourcing cost will decrease unemployment.
Keywords: E23; E24; H22; J23; J33; J82; 330; Flexible outsourcing; profit sharing; labour market imperfection; employee effort; equilibrium unemployment; Outsourcing; Erfolgsbeteiligung; Lohnverhandlungen; Arbeitslosigkeit; Arbeitsmarkttheorie; Unvollkommener Markt; Theorie